1986
DOI: 10.1104/pp.82.4.909
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Phytochrome Regulation of Gibberellin A20 3β-Hydroxylation in Shoots of Dwarf (lele) Pisum sativum L.

Abstract: The effect of light on the dwarfing allele, le, in Pisum sativum L. was tested as the growth response to gibberellins prior to or beyond the presumed block in the gibberellin biosynthetic pathway. The response to the substrate (GA20), the product (GA1), and a nonendogenous early precursor (steviol) was compared in plants bearing the normal Le and the deficient lele genotypes in plants made low in gibberellin content genetically (nana lines) or by paclobutrazol treatment to tall (cv Alaska) and dwarf (cv Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
39
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 9 publications
5
39
1
Order By: Relevance
“…9 responded to GA20 in the dark, even though this GA elicited no growth response in red light when applied in the same manner and at the same dosages (1,19). It was postulated that the conversion of GA20 to GA, is increased in the dwarf in the dark, although an alternative suggestion, namely that GA20 may have biological activity per se in the dark, was also made in both papers.…”
mentioning
confidence: 95%
“…9 responded to GA20 in the dark, even though this GA elicited no growth response in red light when applied in the same manner and at the same dosages (1,19). It was postulated that the conversion of GA20 to GA, is increased in the dwarf in the dark, although an alternative suggestion, namely that GA20 may have biological activity per se in the dark, was also made in both papers.…”
mentioning
confidence: 95%
“…The D. ferox seeds were decoated after 24 h of incubation to achieve a good response to light (25) and immediately irradiated with either FR or FR followed by R. Dark conditions were obtained by enclosing the Petri dishes in black plastic canisters and handling the imbibed seeds only under a dim green safe light. The green, R and FR sources were described previously (8). Irradiations with R and FR were of 20 min and carried out at 25°C.…”
Section: Methods and Materials Seeds And Incubation Conditionsmentioning
confidence: 99%
“…Micropylar portions were dissected from induced and noninduced seeds at 64 h of incubation, suspended in 100 mm acetate buffer (pH 6.0) and incubated for an additional 8 h, either at 33 or 0°C. The sugar composition of the walls prepared from endosperms dissected from control seeds showed no change after the 8 h incubation at 33C.…”
Section: Degradation In Isolated Micropylar Portionsmentioning
confidence: 99%
“…Reports concerning pea (Campell and Bonner, 1986) and cowpea (García-Martínez et al, 1987) have suggested a basic action of phy through regulation of GA 3p-hydroxylation, namely in the conversion of inactive GA,, into active GA,. In cucumber, the most abundant (and most active when applied) 3P-hydroxylated GA is GA, (Nakayama et al, 1989), which is biosynthesized from GA, by 3P-hydroxylation.…”
Section: Phyb and Ca 3p-hydroxylationmentioning
confidence: 99%
“…Furthermore, the metabolism of GA has been shown to be affected by light exposure in dark-grown pea (Sponsel, 1986) or lettuce seedlings (Toyomasu et al, 1992). GA, biosynthesis has been indicated to be under phy control during de-etiolation in pea (Campell and Bonner, 1986) or after R or FR pulses increase in active GA, was found, but the mutant was observed to be "GA hypersensitive" (Reid and Ross, 1988;Weller et al, 1994). In rice mesocotyls, phy activation decreases GA "sensitivity" (Nick and Furuya, 1993).…”
mentioning
confidence: 99%